Pengaruh Pendidikan, Kesehatan, Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Kota-Kota Di Sumatera Barat - Alda Dwi Lestari; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study is intended to be determined; (1) the impact of the economic growth  in west Sumatra’s cities on its parameters, the level of educations that accompanies the average length of school education; (2) the impact of economic growth in west Sumatra cities on health levels and their parameters, or life expectancy; (3) the influence of the economic growth of cities in West Sumatra on the government contest with the parameter, namely the number of government contests. This research is descriptive and associative. The data used is secondary data from 2004 to 2019 obtained from related institutions. This study uses panel data regression with the selected model, namely the Random Effect Model assisted by Eviews 9 software, to find out how the influence of the dependent variable on the dependent variable. The results show that education, health, and spending have a significant impact on West Sumatra’s economic growth cities at the same time. In addition, Part (1)education has an important and positive impact on the economic growth of cities in West Sumatera; (2) Health has a significant but negative impact on the economic growth of cities in West Sumatra (3) Government competition has an important and positive impact on the economic growth of cities in West Sumatera.